Effects of different photoperiods on melatonin level, cecal microbiota and breast muscle morphology of broiler chickens - Yu, Miao; Xu, Mengjie; Wang, Guangju; Feng, Jinghai; Zhang, Minhong (Frontiers in Microbiology, 2025)
Long photoperiods are often characterized by enhanced oxidative stress-induced damage to skeletal muscle, reduced melatonin (MT) levels and intestinal microbiota dysfunction in broilers. In this study, we aimed to investigate the association of breast muscle morphology with melatonin levels and the cecal microbiota of broilers under different photoperiods. A total of 216 healthy 5-day-old Arbor Acres (AA) male broilers were randomly assigned to 12 L:12D, 18 L:6D and 24 L:0D photoperiods for 4 weeks (L = hours of light, D = hours of darkness). The concentration of inflammatory factors and MT concentrations was measured using ELISA kits, whereas breast muscle morphology was examined through the hematoxylin (H) and eosin (E) staining, and microbiota composition was identified through 16 s rRNA analysis. Extended light exposure significantly improved the growth rate of broilers, but significantly decreased feed efficiency (FE). Furthermore, it upregulated the concentration of IL-1β, IL-6 and TNF-α and induced an abnormal breast muscle morphology. Extended light exposure significantly decreased MT levels in the hypothalamus, cecum and breast muscle, while triggering the cecal microbiota composition disorder. Specifically, there was significant alteration to the dominant bacterial phylum, following exposure to long photoperiods, with the abundance of Firmicutes decreasing and the abundance of Bacteroidota increasing. Notably, the relative abundance of Lactobacillus showed a positive correlation with MT levels and a negative correlation with inflammatory cytokines. In conclusion, the present findings indicated that extended light exposure reduced the MT levels, which were related to disturbed cecal microbiota, damaging breast muscle morphology and inducing breast muscle inflammation in broilers.